The Effect of a Single Session of Exhaustive Aerobic Activity Combined with Negative Air Ions on Certain Pulmonary Functional Indices in Active Individual - Younesian, Ali; khaksari, samaneh; gholami, Farhad; Keikha, Mojtaba (Shahroud Journal of Medical Sciences, 2025)
Background: The present study aimed to investigate the effect of a single session of exhaustive aerobic activity combined with negative air ion inhalation on certain pulmonary functional indices in active individuals.Methods: Forty physical education students from Shahrood University of Technology, with a mean age of 22.70±0.61 years and a body mass index (BMI) of 21.59±0.74 kg/m², voluntarily participated in the study. This study was designed as a semi-experimental, double-blind crossover trial. Participants were randomly divided into two groups: one exposed to negative air ions and the other not exposed. Both groups performed the Bruce test, with the protocol repeated after one week while the environmental conditions were reversed. Spirometry was conducted to measure pulmonary indices in two conditions: during exercise with ion exposure (before entering the isolated room and immediately after the Bruce test) and without ion exposure (before and immediately after the test). The data were analyzed using paired t-tests and Wilcoxon tests in SPSS software version 24.Results: The results indicated that negative air ions significantly improved (P-value<0.05) forced vital capacity (FVC) (P-value=0.015), forced expiratory volume in the first second (FEV1) (P-value=0.001), the FEV1/FVC ratio (P-value=0.001), and forced expiratory flow at 25-75% of the pulmonary volume (FEF25-75%) (P-value=0.001).Conclusions: In conclusion, a single session of negative air ion exposure during exhaustive aerobic exercise significantly improved pulmonary function indices, suggesting potential benefits for respiratory performance.